Masoquismo. Un seguimiento del concepto en la obra freudiana (2010)
ABSTRACT: This letter corresponds to a state of affairs relating to the subject of masochism, based on the considerations taken by Freud in the vast field of psychoanalysis. We have taken some of the texts as part of its first development of drive theory and formulations corresponding to the first topical, where addresses the issue in draft form. Also, we have adhered in particular to a couple of writings on masochism in which he describes more fully this enigmatic phenomenon, which are closer to their theoretical elaborations of the second topography. The claim then lies on accounting restatements made in the insights of masochism, which ultimately conceived as a constitutional aspect of sexuality in humans, which can turn into perversion.